Thomas Dickason (Ship) correspondence - Thomas Dickason (Ship)
Anonymous letter (1867 May 5-19; Cape Navarin, Bering Sea) written from the ship Thomas Dickason of New Bedford, Mass., Nathaniel Jernegan, master. The writer noted whales caught as well as a visit from O. G. Robinson, master of the bark Active, also of New Bedford.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Jernegan, Nathaniel; Robinson, O. G; Active (Bark : 1839-1874); Whaling -- Bering Sea; Whaling -- Massachusetts -- New Bedford